2013
DOI: 10.1016/j.pmrj.2013.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Reasons for Return to the Primary Acute Care Service Among Patients With Lymphoma Undergoing Inpatient Rehabilitation

Abstract: Objective To assess the frequency and risk factors for return to the primary acute care service among lymphoma patients undergoing inpatient rehabilitation. Design Retrospective study. Setting Tertiary referral-based cancer center. Patients All patients with a history of lymphoma admitted to inpatient rehabilitation between October 1, 2003 and January 30, 2013. Main Outcome Measures Items analyzed from patient records included return to the primary acute care service with demographic information, lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…Reported readmission rates among cancer patients in inpatient rehabilitation in the United States have ranged from 17% to 35%. 8,4244 We found that among all cancer patients in our cohort, 16% were discharged to acute care. In addition, we also found that patients with blood and lymphatic cancers were most likely to be discharged back to the acute care setting (28%); other studies 8,44,45 have also reported leukemia and lymphoma patients as having a higher likelihood of discharge from inpatient rehabilitation to acute care settings (33% and 38%, respectively).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Reported readmission rates among cancer patients in inpatient rehabilitation in the United States have ranged from 17% to 35%. 8,4244 We found that among all cancer patients in our cohort, 16% were discharged to acute care. In addition, we also found that patients with blood and lymphatic cancers were most likely to be discharged back to the acute care setting (28%); other studies 8,44,45 have also reported leukemia and lymphoma patients as having a higher likelihood of discharge from inpatient rehabilitation to acute care settings (33% and 38%, respectively).…”
Section: Discussionmentioning
confidence: 68%
“…8,4244 We found that among all cancer patients in our cohort, 16% were discharged to acute care. In addition, we also found that patients with blood and lymphatic cancers were most likely to be discharged back to the acute care setting (28%); other studies 8,44,45 have also reported leukemia and lymphoma patients as having a higher likelihood of discharge from inpatient rehabilitation to acute care settings (33% and 38%, respectively). However, we do not have data as to how many of these cancer patients would have been readmitted to acute care if they had not received the inpatient rehabilitation, nor do we know how many of these readmissions were planned for additional cancer treatment.…”
Section: Discussionmentioning
confidence: 68%
“…As it is difficult to assess the severity of any complications that have occurred, we have chosen the procedure that is often used in this context: we took premature discontinuation of the rehabilitation as a criterion for serious complications during the rehabilitation stay (Alam, Wilson, & Vargo, ; Asher et al, ; Fu et al, , ; Fu, Lee, Smith, & Bruera, ; Fu, Lee, Smith, Guo, et al, ; Guo, Persyn, Palmer, & Bruera, ). In order to be able to assess whether rehabilitation stays of patients with haemato‐oncological diseases have to be discontinued particularly frequently in our rehabilitation facility, we compared the frequency of termination of rehabilitation stay in patients with solid tumours with those who suffer from a haemato‐oncological disease.…”
Section: Methodsmentioning
confidence: 99%
“…We investigated to what extent the risk factors investigated so far like age, body mass index (BMI), serum albumin deficiency, gender, renal function, leucocytes, thrombocytes, haemoglobin value, CRP, antimycotic, antibiotic or antiviral agents and the level of remission at the beginning of rehabilitation (Asher et al, ; Fu et al, ; Fu, Lee, Smith, & Bruera, ; Fu, Lee, Smith, Guo, et al, ; ; Guo et al, ) are true for our patients. We analysed the data of all patients with haemato‐oncological diseases and separately of those after high‐dose chemotherapy with allogeneic stem cell transplantation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation